2021
DOI: 10.1111/epi.16823
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated long‐term forgetting in focal epilepsy: Do interictal spikes during sleep matter?

Abstract: Accelerated long‐term forgetting (ALF) is a particular form of amnesia mostly encountered in focal epilepsy, particularly in temporal lobe epilepsy. This type of memory loss is characterized by an impairment of long‐term consolidation of declarative memory, and its mechanisms remain poorly understood. In particular, the respective contribution of lesion, seizures, interictal epileptic discharges, and sleep is still debated. Here, we provide an overview of the relationships intertwining epilepsy, sleep, and mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 86 publications
(155 reference statements)
0
15
0
Order By: Relevance
“…Preeminent hypotheses to explain memory complaint in the epileptic population have been (1) the influence of depressive mood, psychological distress, and disturbance of attentional functions 37 ; (2) the interference of medication on memory processes 38 ; and (3) the role of IEDs, especially during sleep. 39,40 The first and second hypotheses lack evidence or are supported by inconsistent or scarce results. 41 Our results do not corroborate these 2 hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…Preeminent hypotheses to explain memory complaint in the epileptic population have been (1) the influence of depressive mood, psychological distress, and disturbance of attentional functions 37 ; (2) the interference of medication on memory processes 38 ; and (3) the role of IEDs, especially during sleep. 39,40 The first and second hypotheses lack evidence or are supported by inconsistent or scarce results. 41 Our results do not corroborate these 2 hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is now clear evidence in animals and humans that IEDs can result in cognitive impairment, especially if they are frequent and occur during important periods of brain development [23]. It is also widely accepted that sleep is relevant for memory consolidation and other cognitive processes [18,24] and that IEDs during sleep and sleep disruption in patients with epilepsy have a negative impact on cognitive functioning [19,25]. As for other newly developed ASMs, previous studies of cannabidiol treatment in epilepsy therapy also focused on seizure outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that IISs disrupt memory and cognition in both animal models [32] and epileptic patients [33] . Recent studies indicate that this is possibly due to intrahippocampal IISs disrupting memory consolidation during sleep involving the hippocampal and cortical circuits [34] , [35] . Those results suggest that IISs could be “hijacking” and disturbing normal memory processes [36] , [37] .…”
Section: Seizure Related Consolidation and Memory Related Changes Dur...mentioning
confidence: 99%